Novel features of asymmetric nuclear matter from terrestrial experiments and astrophysical observations of neutron stars - Miyatsu, Tsuyoshi; Cheoun, Myung-Ki; Kim, Kyungsik; Saito, Koichi (Frontiers in Physics, 2025)
The accurate measurement of neutron skin thickness of 208Pb by the PREX Collaboration suggests a large value of the nuclear symmetry energy slope parameter, L, whereas the smaller L is preferred to account for the small neutron-star radii from NICER observations. To resolve this discrepancy between nuclear experiments and astrophysical observations, new effective interactions have been developed using relativistic mean-field models with the isoscalar- and isovector-meson mixing. We investigate the effects of δ-nucleon coupling and σ–δ mixing on the ground-state properties of finite nuclei, as well as the characteristics of isospin-asymmetric nuclear matter and neutron stars. Additionally, we explore the role of the quartic ρ-meson self-interaction in dense nuclear matter to mitigate the stiff equation of state for neutron stars resulting from the large δ-nucleon coupling. It is found that the nuclear symmetry energy undergoes a sudden softening at approximately twice the saturation density of nuclear matter, taking into account the PREX-2 result, the recent NICER observation of PSR J0437−4715, and the binary neutron star merger, GW170817.